2014
DOI: 10.1155/2014/903259
|View full text |Cite
|
Sign up to set email alerts
|

The Role of TWIST in Angiogenesis and Cell Migration in Giant Cell Tumor of Bone

Abstract: Giant cell tumor of bone (GCT) is a bone tumor consisting of numerous multinucleated osteoclastic giant cells involved in bone resorption and neoplastic osteoblast-like stromal cells responsible for tumor growth. The tumor occasionally metastasizes to the lung; however, factors leading to metastasis in this tumor are unknown. The TWIST-1 protein (also referred to as TWIST) has been suggested to be involved in epithelial-mesenchymal transition (EMT) and tumor progression in some cancers. In this study we invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…MMPs help in the degradation of the extracellular matrix (ECM) and allow tumors to lose their epithelial characteristics and to acquire mesenchymal phenotypes that are highly regulated by transcriptional factors such as Zeb1, Slug, Snail, TGF-β, and Twist [32,33]. Some of the transcriptional factors have been reported to play a role in angiogenesis [34]. Some studies have reported that the Wnt pathway plays an important role in promoting EMT and angiogenesis in cancer.…”
Section: Discussionmentioning
confidence: 99%
“…MMPs help in the degradation of the extracellular matrix (ECM) and allow tumors to lose their epithelial characteristics and to acquire mesenchymal phenotypes that are highly regulated by transcriptional factors such as Zeb1, Slug, Snail, TGF-β, and Twist [32,33]. Some of the transcriptional factors have been reported to play a role in angiogenesis [34]. Some studies have reported that the Wnt pathway plays an important role in promoting EMT and angiogenesis in cancer.…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that Twist1 promoted melanoma metastasis and growth, which was accompanied by the up-regulation of several vascular growth factors and receptors, including VEGF and MMP-1 55 56 . MMP-2 and MMP-9 can also be regulated by Twist1 and involved in Twist1-induced promotion of metastasis 57 58 . Both VEGF and MMPs are the molecular targets of STAT3.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, this protein plays multiple roles in cancers and mediates cell migration and differentiation. In addition, some reports indicated that TWIST1 is associated with angiogenesis and stemness in various cancers [11][12][13]. As described earlier in a review report, overexpression and role of TWIST1 were observed in various cancers such as prostatic cancer, gastric cancer, breast cancer, and CRC [11].…”
Section: Introductionmentioning
confidence: 71%